Technical experience with tempera paintings in a bachelor degree course in Turkey - Gonca Erim; Ismail Tetikci; Remziye Ersoy (Institute of Advanced Engineering and Science, 2021)
This article aims to understand the place of the tempera technique in art history, which is thought to be encountered for the first time by art education undergraduate students, and to determine the effects on the participants after the application. The study consists of the findings and results of the first and second research questions in the master thesis “Tempera technique and its use in the course of painting courses on undergraduate level.” In this study the “case study” pattern was used, and is one of the qualitative research approaches. The participants of the research are eight students studying in Bursa Uludag University, Faculty of Education, Department of Fine Arts Education in the 2018-2019 academic year. The data collection tools of literature review and two interview forms interview were used. The findings obtained were evaluated by thematic analysis technique. According to the findings obtained in the research, it was observed that the participants did not have prior knowledge about the tempera technique before oral presentation and application. It was concluded that there were differences in the levels of interest and knowledge after the teaching process, and that there were positive changes in their opinions regarding the technique.